The Influence Of Profitability Rasio On Stock Performance With Return Market Control Variabel In The Telecomunication Sub-Sector Listed On The Indonesia Stock Exchange Before, During and After Covid 19 - Sindi Sri Deviana Manalu; Jonny Siagian; Ganda T. Hutapea (Universitas Kristen Indonesia, 2024)
Knowing how the Profitability Ratio affects Stock Performance is the purpose of this study where the profitability ratio uses Earning Yield (EY) and Return On Equity (ROE) indicators and stock performance measured by Stock Return and Stock Risk. In There is a control variable, namely Return Market and the object under study is a telecommunications company listed on IDX with the data taken is data for the period before Covid 19 (2018-2019), the period during Covid 19 (2020-2021) and the period after Covid 19 (2022). Regression analysis using panel data and descriptive analysis, classical assumptions, F test, T test and R2 are used which are processed using the Eviews 12. the number of research samples is 4 companies taken by purposive sampling method and the type of research data is secondary data. The test results on stock returns show that the profitability ratio in the study period did not have a significant effect while the Return Market only had a positive and significant effect in the period during Covid 19. Testing of stock Risk shows that in the period before Covid 19 the profitability ratio has a significant effect while the Return Market is not significant, the period during Covid 19 the research variables have no significant effect and in the period after Covid 19 a significant effect is only shown by earning yield. Testing of stock returns simultaneously only in the period during Covid 19, while testing of Risk only in the period before and after Covid 19. Keywords: Stock Return, Stock Risk, Earning Yield, Return On Equity (ROE) Return Market